Potable water membrane filtration system - Lee, Bee Yee. (2008)
This study was conducted to investigate the ability of selected hollow fibre membranes (microfiltration and ultrafiltration) to treat Nanyang Lake Water which has similar characteristics to reservoir water. The ions removal efficiency of the membranes is also looked into. Two pre-treatment methods, coagulation and sand filtration, were highlighted in this report to study their competency on extending the lifespan of the membranes. Small scale membrane systems are used to increase the scope of investigation and the efficiency of the membrane is determined by the measurement of certain water quality parameters. Results showed that pre –treatment of the process feed stream has improved the flux without compromising the permeate quality. Coagulation with 30mg/L alum, being the most efficient pre-treatment studied, has improved the flux of the membrane from 1.2 m3/m2.d to 1.74 m3/m2.d. It has also effectively reduced the turbidity of the Nanyang Lake Water from 18.8 NTU to 0.09 NTU (permeate quality). The membranes studied were able to improve the quality of the Nanyang Lake Water but proved to be inefficient in the removal of dissolved ions. Hence, both microfiltration and ultrafiltration are better utilized as pre-treatment to nanofiltration and reverse osmosis process.